The impact of organisational structures on service delivery : a case study of the uMgungundlovu District Municipality - Mlotshwa, Sibongile G. (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2007.